Antibody Mediated Transduction of Therapeutic Proteins into Living Cells - James E. Hansen; Richard H. Weisbart; Robert N. Nishimura (The Scientific World Journal)
Protein therapy refers to the direct delivery of therapeutic proteins to cells and tissues with the goal of ameliorating or modifying a disease process. Current techniques for delivering proteins across cell membranes include taking advantage of receptor-mediated endocytosis or using protein transduction domains that penetrate directly into cells. The most commonly used protein transduction domains are small cell-penetrating peptides derived from such proteins as the HIV-1 Tat protein. A novel protein transduction domain developed as the single chain fragment (Fv) of a murine anti-DNA autoantibody, mAb 3E10, has recently been developed and used to deliver biologically active proteins to living cells in vitro. This review will provide a brief overview of the development of the Fv fragment and provide a summary of recent studies using Fv to deliver therapeutic peptides and proteins (such as a C-terminal p53 peptide, C-terminal p53 antibody fragment, full-length p53, and micro-dystrophin) to cells.